Quality of life in prostate cancer survivors in developing countries: The case of the Gaza Strip, Palestine - Nasser Ibrahim Abu El Noor; Mysoon Khalil Abu El Noor (Tehran University of Medical Sciences, 2015)
Background & Aim: Prostate cancer is one of the most common cancers in males and the second leading cause of cancer-related deaths in Palestine. Although, many studies were conducted in de- veloped countries to evaluate quality of life (QOL) in survivors of prostate cancer, the researchers could not find any study that was conducted in a developing country including Palestine. Therefore, the purpose of this study was to evaluate the QOL of prostate cancer survivors residing in Gaza Strip, Palestine, as an example of a developing country, and compare it with the literature. Methods & Materials: A total of a 121 men who were diagnosed with prostate cancer and live in Gaza Strip participated in this cross-sectional study. The University of California at Los Angeles Prostate-Specific Index including the RAND 36-Item Health Survey v2 was used to assess QOL of participants. Results: Age of participants' ranged between 52 and 89 years with a mean of 71.80 (SD 7.66). The greatest majority of participants (n = 94, 77.67%) were diagnosed with prostate cancer after the age of 60. The mean scores for the entire general QOL items was 47.93 (SD = 22.46) and the mean for all Prostate Cancer Index - University of California items was 44.20 (SD = 16.16). Conclusion: Prostate cancer survivors living in Gaza Strip, Palestine have lower level of QOL than their counterparts who live in developed courtiers. These differences could be related to early screening and advanced technology used to treat prostate cancer in developed countries. Health care providers and health care policy makers need to improve provided health care services and introduce screening method to diagnose prostate cancer early. Further studies are recommended to compare QOL of prostate cancer survivors living in developing countries and developed countries.